On the Polar Bias in Ice Core 10Be Data. Issue 4 (9th February 2023) - Adolphi, F.; Herbst, K.; Nilsson, A.; Panovska, S.
Abstract: Cosmogenic radionuclide records from polar ice cores provide unique insights into past cosmic ray flux variations. They allow reconstructions of past solar activity, space weather, and geomagnetic field changes, and provide insights into past carbon cycle changes. However, all these applications rely on the proportionality of the ice core radionuclide records to the global mean production rate changes. This premise has been long debated from a model and data‐perspective. Here, we address this issue through atmospheric mixing model experiments and comparison to independent data. We find that all mixing scenarios, which do not assume complete tropospheric mixing, result in a polar bias. This bias is more prominent for geomagnetic field changes than solar modulation changes. The most likely scenario, supported by independent geomagnetic field records and marine 10 Be during the Laschamps geomagnetic field minimum, results in a dampening of geomagnetic field induced changes by 23%–37% and an enhancement of solar‐induced changes by 7%–8%. During the Holocene, we do not find conclusive evidence for a polar bias. We propose a correction function that allows deconvolving the glacial ice core record in order to restore proportionality to the global mean signal. Plain Language Summary: Ice core records of cosmogenic radionuclides (e.g., 10 Be) are unique archives providing information on past changes in galactic and solar cosmic ray fluxes. The atmospheric production rates vary in response to changes of the cosmic ray flux, which in turn is modulated by solar and geomagnetic shielding. Typically, it is assumed that the deposition of 10 Be on the ice varies in proportion to changes in its atmospheric production rate. However, this assumption has been questioned early on, since the geomagnetic shielding against cosmic rays depends on the geomagnetic latitude, being essentially zero at the ice‐core locations. It was proposed, that ice cores may suffer from a "polar bias" which dampens the geomagnetic field signal and enhances the solar signal in ice core 10 Be, thus questioning the use of ice‐core 10 Be‐data as proxies for global cosmogenic radionuclide production rate changes. Here, we revisit this hypothesis using mixing model experiments in conjunction with a compilation of 10 Be data from high and low‐latitude archives and geomagnetic field models. We deduce that a polar bias is likely present in glacial ice‐core 10 Be‐records and provide a simple method to approximately restore the proportionality of ice core 10 Be data to global production rate changes. Key Points: Mixing‐model experiments and independent data suggest that ice‐core 10 Be‐records do not capture a global‐mean signal During the glacial, modulation by geomagnetic field changes is dampened by ∼23%. Effects of solar activity changes are enhanced by ∼7% A transfer function is proposed that restores the approximate proportionality of ice core data to global production rate changes